(untitled) (London Journal of Research In Science: Natural and Formal, 2025)
Based on previous research, this paper proposes are volutionary hypothesis about the essence of electrons. The study first draws on the innovative description of the wave-particle duality of photons in "Hypothesis on the Spatial Motion Mode of Photons", combines the theoretical derivation of the possibility of the existence of ether space in "Several Conjectures on the Existence of Ether", and the breakthrough idea of the electron structure model, and creatively puts forward the "Hypothesis on the Ether Space Structure of Electrons". This hypothesis challenges the traditional view in theories that regards electrons as point particles, and argues that electrons are essentially entities with a wave-particle dualitye ther space structure. This study systematically elaborates on the uniquee ther vortex structure and quantum dynamic behavior of electrons, constructs a brand-new theoretical framework to explain the wave-particle duality of electrons, and provides new understanding the theoretical principles of basic particles such as electrons. This theoretical innovation not only helps to deepen the understanding of the essence of electrons, but may also open up newr esearch paths for unifying quantum mechanics and classical physics.